Modelling of Pressurised Water Supply Networks that May Exhibit Transient Low Pressure - Open Channel Flow Conditions - Byakika, Stephen Nyende (Vaal University of Technology, 2011)
Growing demand for water due to increasing populations, industrialisation and water consuming lifestyles puts stress on existing water supply systems. To cater for the rising demand, water distribution networks are expanded beyond their design capacities and this creates transient “low-pressure-open-channel flow” (LPOCF) conditions. Current water supply models use “demand driven approach” (DDA) methodology which is not able to simulate transient LPOCF conditions, that poses an impediment to management/analysis of pressure-deficient networks. With a case study of the water supply network of Kampala City, LPOCF conditions were studied in this research. A “pressure/head driven approach” (PDA/HDA) was used in order to determine what demand is enabled by particular nodal pressures. Conversion of free surface to pressurised flow was analysed and modelled, with a view to clearly understanding occurrence of this phenomenon. The research demonstrated that if adequate pressures and flows are to be maintained, effectiveness of the water distribution network should be given as much attention as water production capacity. The research also indicated that when network pressures are low, the head-driven approach to water distribution modelling gives more accurate results than the traditional demand-driven methodology. Coexistence of free-surface and pressurised flow in networks prone to LPOCF conditions was confirmed and modelled. Results obtained highlighted the advantages of developing fully dynamic and transient models in the solution of transient LPOCF conditions in water distribution networks. Models developed allow application of PDA/HDA and DDA methodologies in systems that may exhibit LPOCF conditions thus enabling identification, understanding and analysis of the status of all sections of the network. These culminated in the development of a DSS to guide operational decisions that can be made to optimise network performance.
D. Tech. (Department of Civil Engineering and Building, Faculty of Engineering and Technology), Vaal University of Technology
Keywords: water supply, simulation, water distribution; Water-supply; Water-supply engineering -- Data processing.